Is Voluntary Repatriation the Preferred Durable Solution? The View of Refugees in South Africa - Khan, Fatima (African Human Mobility Review, 2021)
Voluntary repatriation as the preferred durable solution for refugees has attractedmuch scholarly attention and the existing literature highlights the complexities of theprocess. This paper attempts to answer the question of when return can be consideredas truly voluntary and preferred. To answer this question, the paper considers reasonsoffered by refugees themselves. The percentage of voluntary repatriation applicationsby refugees living in South Africa is low in relation to the number of refugees living inthe country. However, reasons why refugees might choose to repatriate are still worthyof interrogation if we are to truly establish whether it is a preferred solution. Refugees’answers illustrate that they are not always completely free to make choices. They mayindicate consent, but consent does not necessarily indicate a preference. This paper incorporatesa study which reveals that refugees choosing to repatriate from South Africaare indeed very small in number, despite the vigorous attempts of the United NationsHigh Commissioner for Refugees (UNHCR) at promoting voluntary repatriation. Itfurther reveals that this can be partly attributed to the fact that in an urban settingsuch as South Africa with a rights-based framework, refugees are often able to betterintegrate into their host society without the direct assistance of the UNHCR as theywould do in a camp-based setting. As such, assumptions that voluntary repatriation isa preferred durable solution for all refugees, need to be interrogated.